2023
DOI: 10.1101/2023.06.25.546465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsically Disordered Regions Promote Protein Refoldability and Facilitate Retrieval from Biomolecular Condensates

Philip To,
Atharva M. Bhagwat,
Haley E. Tarbox
et al.

Abstract: Many eukaryotic proteins contain intrinsically disordered regions (IDRs) that intersperse globular folded domains, in contrast with bacterial proteins which are typically highly globular. Recent years have seen great progress in identifying biological functions associated with these elusive protein sequence: in specific cases, they mediate liquid-liquid phase separation, perform molecular recognition, or act as sensors to changes in the environment. Nevertheless, only a small number of IDRs have annotated func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…4 F ). One possibility is that proteins with intrinsically disordered regions are better able to assume a native conformation after stress as compared with proteins with more structured domains ( 54 ). Recent work in Drosophila found that RNP granules increase in size during aging, but do not display changes in Fluorescence Recovery After Photobleaching (FRAP) signal.…”
Section: Discussionmentioning
confidence: 99%
“…4 F ). One possibility is that proteins with intrinsically disordered regions are better able to assume a native conformation after stress as compared with proteins with more structured domains ( 54 ). Recent work in Drosophila found that RNP granules increase in size during aging, but do not display changes in Fluorescence Recovery After Photobleaching (FRAP) signal.…”
Section: Discussionmentioning
confidence: 99%
“…As a very brief intro, biomolecular condensates generally require multivalent interactions in order to form a three dimensional network (Li et al, 2012;Brangwynne et al, 2015;Choi et al, 2020). One useful model for these multivalent interactions is that interacting "stickers" are connected by a flexible (Ali et al, 2023) stress granules (Cherkasov et al, 2013;Kroschwald et al, 2015;Walters et al, 2015;Yoo et al, 2022;To et al, 2023) Hsp40 DNAJB1 FUS (Gu et al, 2020) R I α (Zhang et al, 2020) Hsp70 Ssa1/2/3/4 Std1 (Simpson-Lavy et al, 2017) purinosome (French et al, 2013;Pedley et al, 2018; stress granules (Cherkasov et al, 2013;Kroschwald et al, 2015;Walters et al, 2015;Yoo et al, 2022;To et al, 2023) Hsp70 HSPA1A/HSPA1/HSPA5/ HSPA6/HSPA8…”
Section: Integrating Chaperones Into a Conceptual Framework Of Conden...mentioning
confidence: 99%
“…TDP-43 (Udan-Johns et al, 2014;Gu et al, 2021;Yu et al, 2021;François-Moutal et al, 2022); REV-ERBα (Zhu et al, 2023) RIα (Zhang et al, 2020(Zhang et al, , 2023; EML4-Alk (Zhang et al, 2023) Hsp90 Hsp90α/Hsp90β purinosome (French et al, 2013;Pedley et al, 2018; AAA+ Hsp104 Std1 (Simpson-Lavy et al, 2017) stress granules (Cherkasov et al, 2013;Kroschwald et al, 2015;Walters et al, 2015;Yoo et al, 2022;To et al, 2023) AAA+ VCP stress granules (Erives and Fassler, 2015;Mateju et al, 2017;Wang et al, 2019;Gwon et al, 2021) sHSP Btn2 Ure2 (Kryndushkin et al, 2008;Son and Wickner, 2022); INQ (Malinovska et al, 2012); CtyoQ (Malinovska et al, 2012;Simpson-Lavy et al, 2017) sHSP Hsp42 CytoQ (Specht et al, 2011;Grousl et al, 2018) sporulation-induced condensates (Plante et al, 2023) sHSP Cur1 Std1 (Simpson-Lavy et al, 2017) sHSP Hsp27 p62/SQSTM1 (Gallagher and Holzbaur, 2023); FUS (Liu et al, 2020) sHSP HspB1 TDP-43 (Lu et al, 2022) sHSP HspB8 FUS (Boczek et al, 2021) nuclear transport receptors Kapβ2/KPNB1 FUS (Guo et al, 2018;Hofweber et al, 2018;Qamar et al, 2018;Yoshizawa et al, 2018;…”
Section: Integrating Chaperones Into a Conceptual Framework Of Conden...mentioning
confidence: 99%
“…Moreover, these conformational biases can influence or even determine IDR function. The average conformational properties of IDR ensembles have been shown to tune binding to partner proteins 4 , refolding of tethered folded domains 5 , enzymatic reaction rates 6 , and the ability to form higher-order oligomers and condensates 7 . Thus, IDRs are disordered but not unstructured, and an emerging paradigm suggests that IDR function depends on a combination of sequence features, ensemble properties, and linear motifs ( Fig.…”
Section: Introductionmentioning
confidence: 99%